PENDIDIKAN SENI TARI MELALUI PENDEKATAN EKSPRESI BEBAS, DISIPLIN ILMU, DAN MULTIKULTURAL SEBAGAI UPAYA PENINGKATAN KREATIVITAS SISWA - Kusumastuti, Eny (Harmonia: Journal of Arts Research and Education, 2010)
The problem of the study is how the process of the implementation of dance education through the approach of free expression, disciplines and multicultural as an effort to increase students' creativity. The study employed qualitative approach with the researcher herself as the research instrument. Data collection techniques included focused interviews, participant observation, and study documentation. Data analysis was done by reducing, clarifying, describing, concluding, and interpreting all the information selectively. The results show the process of implementation of dance education is inseparable from the teaching-learning process, which covers: curriculum, objectives, teaching materials, methods of teaching and learning activities, facilities and infrastructure, and evaluation. Free expression approach in learning the art of dance is done by providing opportunities for students to develop movements, done through observing objects, image and music. The implementation process of learning the art of dance through discipline approach is done by giving the subject matter theoretically based on scientific viewpoint. The implementation process of learning the art of dance through a multicultural approach is done by introducing, practicing, and doing reformation to the students about the diversity of cultural arts of their homeland. Kata Kunci: pendidikan seni tari, pendekatan ekspresi bebas, multikultural, kreativitas